Improvement in social welfare division among buyer and supplier in LP based market clearing method in day-ahead electricity market. Issue 4 (2nd October 2019) - Shah, Devnath; Chatterjee, Saibal
ABSTRACT: Most Electric Power Exchange (PX) around the world employs Linear Programming (LP) based method for step-wise market clearing in Day-Ahead Electricity Market (DAM). Market clearing involves calculation of Market Clearing Volume (MCV) and Market Clearing Price (MCP) for various time blocks. LP based method gives accurate results when there exists unique intersection point between cumulative supply and cumulative demand curve. It requires additional information to handle multiple intersection points. But MCP obtained using LP based method leads to an unfair social welfare division among suppliers and buyers. Therefore, this paper investigates all possible cases where there exists an unfair social welfare division among suppliers and buyers. Modification to the existing LP based market clearing method to obtain that market equilibrium point which results in fair social welfare division is also discussed. The performance of the proposed method to obtain MCV & MCP which ensures fair social welfare division between suppliers and buyers under six different cases is tested using a simple test problem and DAM data obtained from Indian Energy Exchange (IEX) websites. Results clearly show that the proposed method is capable enough to generate market equilibrium which results in fair social welfare division among buyers and suppliers. Abbreviations: PX - Electric Power Exchange; LP - Linear Programming; DAM - Day Ahead Electricity Market; MCV - Market Clearing Volume; MCP - Market Clearing Price; IEX - Indian Energy Exchange; USD - United States Dollar; REC - Renewable Energy; TAM - Term Ahead Market; CERC - Central Electricity Regulatory Commission